PENILAIAN KUALITAS PEMAMPATAN CITRA PADA APLIKASI-APLIKASI INSTANT MESSENGER - Khoiru Nurfitri; M. Suyanto; Sukoco . (MULTITEK INDONESIA, 2017)
Useful image compression to compress the file size of the image thus saving storage and speed up the transfer process. This study aims to measuring on the quality of the image as compressed by instant messenger application by comparing the initial image or the input image with the image compression results. The assessment is based on objective criteria by using research methods of comparative research. The objective criteria used is the compression ratio, PSNR, the quality index, and SSIM. From this research it is known that each - each instant messenger applications have a compression ratio that varies. In addition, PSNR, SSIM, and quality index are different too. From the analysis concluded that the order of the image that has a fairly high compression ratio and good quality is the Line